194k views
5 votes
Arithmetic sequences (nth term)​

Arithmetic sequences (nth term)​-example-1
User Binh
by
5.5k points

1 Answer

7 votes

Tick the arithmetic sequences.

In order for a sequence to be arithmetic the relations between their numbers must be the sum of a common ratio, therefore to determine which ones are arithmetic sequence we need to satisfy the following expression:


a_n - a_(n-1) = a_(n-2) - a_(n-3)

The expression just mean that the subtraction of consecutive terms should be equal for position in the sequence.

"1, 5, 9, 13...":


13 - 9 = 5 - 1\\4 = 4

Since the expression is valid, then this is a arithmetic sequence.

"6, 10, 15, 21...:


21 - 15 = 10 - 6\\6 = 4

Since the expression is invalid, then this isn't a arithmetic sequence.

"2, 3, 5, 8...:


8 - 5 = 3 - 2\\3 = 1

Since the expression is invalid, then this isn't a arithmetic sequence.

"2, -4, 8, -16...:


-16- 8 = -4 - 2\\-24 = -6

Since the expression is invalid, then this isn't a arithmetic sequence.

"-1, 2, 5, 8...:


8 - 5 = 2 -(- 1)\\3 = 3

Since the expression is valid, then this is a arithmetic sequence.

"73, 66, 59, 52...:


52 - 59 = 66 - 73\\-7 = -7

Since the expression is valid, then this is a arithmetic sequence.

"6, 1, -4, -9...:


-9 - (-4) = 1 - 6\\-5 = -5

Since the expression is valid, then this is a arithmetic sequence.

"1, 2, 4, 8...:


8 - 4 = 2 - 1\\4 = 1

Since the expression is invalid, then this isn't a arithmetic sequence.

Find the first five terms of the patterns with these nth terms.

For
3n + 3:


3*1 + 3 = 3 + 3 = 6


6 + 3 = 9


9 + 3 = 12


12 + 3 = 15


15 + 3 = 18

(6, 9, 12, 15, 18)

For
9n - 7:


9*1 - 7 = 9 - 7 = 2


2 + 9 = 11


11 + 9 = 20


20 + 9 = 29


29 + 9 = 38

(2,11,20,29,38)

Write down a formula for the nth term of these patterns. The first term is n = 1.

The nth term of any arithmetic sequence is:
a(n) = a(1)*(n - 1)*r

Therefore we need to identify r in each sequence.

For (9,15,21,27,33):


r = 15 - 9 = 6


a(n) = 1*(n - 1)*6 \\a(n) = 6*n - 6

For (-2,-8,-14,-20,-26):


r = -8 - (-2) = -6


a(n) = 1*(n - 1)*(-6)\\a(n) = -6*n + 6

User Robin Ellerkmann
by
6.4k points